Prevention of nitric oxide synthase induction in vascular smooth muscle cells by microtubule depolymerizing agents. - Marczin, N. (Nature Publishing Group, 1993)
We investigated the role of microtubules in the induction of nitric oxide synthase in cultured vascular smooth muscle cells. We found that like interleukin-1 alpha, lipopolysaccharide elicited a time and concentration-dependent accumulation of cyclic GMP via induction of nitric oxide synthase. Nocodazole and colchicine, two chemically distinct microtubule depolymerizing agents, completely prevented lipopolysaccharide- and interleukin-induced (and nitric oxide-mediated) cyclic GMP generation. In contrast to lipopolysaccharide and interleukin-1 alpha, cyclic GMP accumulation in response to sodium nitroprusside, an exogenous nitrovasodilator, was not altered by either nocodazole or colchicine. Our findings demonstrate that microtubule depolymerizing agents inhibit nitric oxide synthase induction and suggest a prominent role for microtubules in mediating the activation of the inducible nitric oxide pathway in smooth muscle cells.